دراسة محتوى التربة المحيطة بمعمل اسمنت طرطوس من بعض المعادن الثقيلة pb, Cd , fe, Cu , Zn , Ni)) - كبيبو عيسى; هيفا سوسن; زيادة ميسون (Latakia University Journal -Biological Sciences Series, 2019)
يهدف البحث إلى تقييم المنطقة شرق معمل اسمنت طرطوس من جهة محتوى التربة من بعض المعادن الثقيلة, تم إجراء أربعة مقاطع ترابية على أبعاد مختلفة شرق معمل اسمنت طرطوس (2000,1000,600,200) م, وأخذت عينات مركبة من أفقين أفق سطحي (15-0)سم, وأفق تحت سطحي (45-15)سم, وقد بينت الدراسة أن محتوى التربة المدروسة من المعادن الثقيلة (حديد, نحاس, زنك) يقع ضمن الحدود الطبيعية للترب, ومع ذلك فقد وجد من خلال معامل تعزيز التربة السطحية أن الموقعين 2000م, 1000م يملكان أكبر قيم لهذا المعامل, فسر ذلك باحتمال تلقي هذين الموقعين لكميات كبيرة من الغبار الاسمنتي ودخان المعمل بسبب ارتفاعهما النسبي مقارنة بالموقعين 600م, 200م (تضاريسية المنطقة), كما امتلك الموقع 200م قيم عالية لمعامل تعزيز التربة السطحية للنيكل والرصاص، ويعود ذلك لقرب الموقع الشديد من المعمل, أما الموقع 600م فقد امتلك أقل قيم لمعامل تعزيز التربة السطحية, مما يدل على تلقيه لأقل كميات من الغبار ودخان المعمل مقارنة بالمواقع الأخرى المدروسة, وقد وجد تلوث تربة بالنيكل, في حين لا يوجد تلوث بالكادميوم. This research aims at evaluating the area to the east of Tartous Cement Plant as to the soil contents of some heavy metals. Soil sections taken from the east of Tartous Cement Plant were of various dimensions (200m, 600m, 1000m, and 2000m). Complex samples were taken from two levels: topsoil layer (0- 15) cm, and sub soil layer (14- 45) cm. Studies revealed that soil content of heavy metals (iron, copper, and zinc) is within soil normal limits. Yet, the coefficient of relative topsoil enhancement (RTE) showed that the two locations 1000m and 2000m have the biggest values of it. It is interpreted that those two locations have possibly received big quantities of cement dust and plant smoke due to their proportional height, compared with locations 200m and 600m (area elevation). In addition, location 200m had high values of this coefficient regarding nickel and lead, which is due to its very close location to the plant. But location 600m had lower values of the coefficient of relative topsoil enhancement, which means receiving smaller quantities of plant’s dust and smoke when compared with the other studied locations. Soil was found contaminated with nickel, but not contaminated with cadmium.